Congenital epidermoid cyst of penis with hypospadias: A case report - Patel, Akhilesh Kumar; Rathore, Nakul Kumar; Deshwali, Ankur; Singh, Abhishek; Kela, Manoj; Sharma, Rajesh; Prasad, Sanjay; Prakash, Advait (Indian Journal of Case Reports, 2019)
The epidermoid cysts are the most common cutaneous cysts and may develop from any parts of the human body. Primary epidermoid cyst with hypospadias in the penis is very rare. Here, we present the case of a slow growing, mobilized; non-tender frenulum of the penis mass in a 44-year-old male patient. Complete excision of the cyst was performed under spinal anesthesia. Histopathological examination confirmed the mass to be an epidermoid cyst. Care must be given during examination to rule out another entity. If thereis any indication, complete excision and hypospadias repair is the best treatment.